Oyster Mushroom (Pleurotus ostreatus) and Okara Flour as Nutritional Enhancers in Wheat Biscuits: A Study on Storage Stability - Emmanuella Ifunanya Nwaudah; Ifeoma Elizabeth Mbaeyi-Nwaoha; Deborah Chinwendu Ofoegbu; Helen Onyeaka (Foods, 2025)
In response to the scarcity and high cost of wheat in Nigeria, this study investigates the potential of oyster mushroom (Pleurotus ostreatus) and okara flour to enhance the nutritional quality and storage stability of wheat biscuits. By incorporating 10–50% oyster mushroom powder into wheat flour, this study observed significant increases in the nutritional profile of the biscuits. The protein content notably increased from 8.26% to 16.12%, while the crude fibre and ash content also saw over a 50% increment. Storage studies revealed that biscuits (baked for 18 min at 180 °C) packaged in cartons within polyethene were more shelf-stable than those in low-density polyethylene (LDPE) bags, maintaining quality over two months at ambient temperature. The inclusion of oyster mushroom and okara flour in wheat biscuits significantly enhances their nutritional value and shelf life, presenting a viable solution to the challenges of wheat scarcity and global malnutrition. The optimal mushroom flour enrichment level was identified at 20% to maintain consumer appeal.